The Importance of Post-Activation Potentiation (PAP) Training on Physical Fitness Preparation for Malaysian Female Hockey Players - Mohar, Kassim; Fariq, Rahman (International Journal of Engineering and Technology, 2018)
A vast amount of research has been performed illustrating that the execution of certain conditioning activities at maximal or near-maximal intensities can acutely enhance subsequent athletic performance with given sufficient recovery. This phenomenon is known as post-activation potentiation (PAP) and its use within the field of strength and conditioning has grown rapidly as performance enhancing effects have been demonstrated within athletic movements such as jumping and sprinting. Objective: The purpose of this study is to analyse the effectiveness of PAP training on sprint performance and power production among Malaysian female hockey player. Methods: A total of 18 well-trained athletes (age 25 ± 3.7; mass 54 ± 4.9; height 160.8 ± 2.8; relative strength half-squat 1.9 ± 0.3; relative strength hex-bar deadlift 1.7 ± 0.5; relative strength hang clean 0.8 ± 0.1) were tested for 20 meter sprint time and counter-movement jump (CMJ) test during the preparation phase. This study used two different groups such as experimental group (EG) and control group (CG) and each player were randomly assigned. Both groups were completed training in twice per week for a period of eight week training program. The EG performed a total of 16 session by having 2 different training blocks. Each block has a period practice of training for 4 weeks and each block also has different types of exercise. Meanwhile, CG completed 16 session based on coach training program and did not practice at the same time with the EG. The study intervention program including pre-test and post-test activities were conducted before and after the study. Result: A data analysis of paired t-test and independent t-test was used and the level of significance in all statistical analyses was set at p ≤ 0.05. The result showed that 8-weeks of EG displayed significantly improved in sprint performance (p ≤ 0.005) and power production (p ≤ 0.005). Moreover, result also revealed a significant difference between EG and CG in sprint performance (p ≤ 0.000) and power production (p ≤ 0.008). Conclusion: In short, the result emphasized the contribution of kinetic and kinematic parameters for sprint and power performance. The EG result seem significant for athletic performance. Therefore, this findings is of great practical interest for coaches and fitness trainers and relevant to female hockey players and consequently maybe used in training program.